First order self-adjoint multipoint quasi-differential operators - (:unkn) unknown (My University, 2018)
In this paper, using the Calkin–Gorbachuk method, the general form of all self-adjoint operators generatedby first order linear singular multipoint quasi-differential expressions in the direct sum of weighted Hilbert spaces ofvector functions has been found. Later on, the geometry of the spectrum set of these type extensions was researched.
Keywords: Matematik